ANALYSIS OF LANDING STATION LOCATION DETERMINATION FOR MARINE CABLE-BASED TSUNAMI EARLY WARNING SYSTEM IN CILACAP, CANTRAL JAVA - Heru Sri Naryanto; Wisyanto Wisyanto (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Cilacap is located on the southern coast of Central Java, facing the confluence of the Indo-Australian Plate and the Eurasian Plate as well as the Megathrust south of Java, so it has a high chance of an earthquake and tsunami disaster. With the issuance of Presidential Regulation (Perpres) No. 93 of 2019 concerning Strengthening and Development of Earthquake Information Systems and Tsunami Early Warning, mandates the implementation of deep sea level tsunamis (buoys) and Cable-Based Tsunameters (CBT). The development of a tsunami early detection system using InaCBT submarine cable technology is the development of the Advanced Cable Based Tsunameter (AdvCBT). For the implementation of the AdvCBT development activities, a submarine cable route is planned from Krui, Pelabuhan Ratu and Cilacap. The location of the landing station (LS) in the form of a power house (PH), communication tower and beach manhole (BMH) must be determined prior to the construction of the AdvCBT infrastructure. Cilacap is one of the places that will be the location of the landing station of the AdvCBT. Scoring is carried out to obtain the best alternative location by considering: land availability, safe elevation against tsunamis, cable routes that do not cut rivers or roads, GSM signal conditions, electricity availability, soil stability, distance from the beach, social conditions of the community, environmental conditions, and safe from other obstacles. Analysis of eleven alternative landing station locations based on the scoring, the results show that the highest score for the alternative location is ALT-09, and ALT-08, both locations are located in Karangbenda, Kec. Adipala, Cilacap Regency, Central Java. Of the eleven (11) alternative landing station locations as a result of the desktop study, it was found that the highest scores for the alternative landing station locations were ALT-09 and ALT-08, both of which were located in Karangbenda, Kec. Adipala, Cilacap Regency, Central Java.